Lembaga Pendidikan Untuk Pencari Ilmu (Suatu Analisa Pendidikan di Aceh) - Zulfadli Zulfadli (Sociology Department Of Syiah Kuala University, 2016)
Looking for legal science fard. Then the government should prepare educational institutions for knowledge seekers. Some of the problems described in this article include; (1) The classification of educational institutions both in Indonesia and in Aceh, (2) Legal seek knowledge, (3) Virtue owner science, (4) Scientists are expected. Educational institutions in Indonesia in the Act could we classify into two groups: the school and outside of school, then it is more detailed division into three forms: (1). Informal, (2). Formal, (3). and non-formal. Formal channel is the institution consisting of primary education, secondary education, and higher education with the kind of education: (1) General, (2) Vocational (3) Academic, (4) Profession, (5) Advocacy, (6). Religious. Levels of education in the kingdom of Aceh Darussalam are as follows: (10) meunasah, (2) rangkang, (3) Boarding School, (4) dayah Tengku Chiek, (5) Baiturrahman association. Seeking knowledge is fard kifayah Shar'ie, if there are people who have studied the law becomes Sunnah for others. But sometimes seek knowledge it becomes fard 'ayn for humans. The virtue of the owner will be taken up science in the world and in the hereafter. Scientists expected is that having insight / knowledge broad and apply their knowledge, both in matters of faith, worship, morals, manners, and muamalah.Keywords: Institute of Education, ScienceIntisariMencari ilmu hukumnya fardhu. Maka pemerintah harus menyiapkan lembaga pendidikan bagi pencari ilmu. Beberapa permasalahan yang diuraikan dalam tulisan ini meliputi; (1) Klasifikasi lembaga pendidikan baik di Indonesia maupun di Aceh, (2) Hukum mencari ilmu, (3) Keutamaan pemilik ilmu, (4) Ilmuwan yang diharapkan. Lembaga pendidikan di indonesia dalam UU bisa kita klasifikasikan menjadi dua kelompok yaitu: sekolah dan luar sekolah, selanjutnya pembagian ini lebih rincinya menjadi tiga bentuk: ( 1). Informal, (2). Formal, (3). dan nonformal. Jalur formal adalah lembaga pendidikan yang terdiri dari pendidikan dasar, pendidikan menengah, dan pendidikan tinggi dengan jenis pendidikan: (1) Umum, (2) Kejuruan, (3) Akademik, (4) Profesi, (5) Advokasi, (6). Keagamaan.Tingkatan pendidikan dalam kerajaan Aceh Darussalam adalah sebagai berikut: (10) Meunasah, (2) Rangkang, (3) Dayah, (4) dayah Tengku Chiek, (5) Jamiah Baiturrahman. Mencari ilmu syar’i adalah fardhu kifayah, apabila ada orang yang sudah mempelajarinya maka hukumnya menjadi sunnah bagi yang lainnya. Tetapi terkadang mencari ilmu itu menjadi fardhu ‘ain bagi manusia. Keutamaan bagi pemilik ilmu akan angkat derajatnya di dunia dan di akhirat. Ilmuwan yang diharapkan adalah yang memiliki wawasan/pengetahuan yang luas serta mengamalkan ilmunya, baik dalam masalah aqidah, ibadah, akhlak, adab, dan muamalah. Kata Kunci: Lembaga Pendidikan, Ilmu